MORPHOMETRIC PARAMETERS OF GROWTH AND DEVELOPMENT OF FETUS OF COWS AND AMINO ACID COMPOSITION OF AMNIOTIC LIQUID - Замазій, А. А. (Scientific Progress & Innovations, 2013)
The data of dynamics of fetus growth and development indicators, and also amino acid composition of amniotic liquid of clinically healthy newborn calves are given. It is established that since the end of the first month of growth and embryo development until the end of the second one its body weight increased in 64,71 times (р<0,001). At the end of the first month of growth and development the embryo mass was only 0,68±0,01 g, amnion volume was 7,08±0,12 ml, and аllantois – 45,40±1,40 ml with a trunk length of a fetus of 0,92±0,01 centimeters. Increase of weight of a fetus on months of growth and development decreases from 64,71 times to 1,45 times, and actually the mass of a fetus body increases from 0,68±0,01 g to 28700,0±5,29 g in comparison with the last month of its growth and development.